Haemoglobin E/Beta Thalassaemia- A Study in BSMMU (Bangabandhu Sheikh Mujib Medical University Journal, 2010)
Background: Thalassaemias and haemoglobinopathies have been found sporadically in every ethnic group and geographic region, they occur with particularly high frequency from the shores of the Mediterranean and Africa through the Middle East, the Indian subcontinent, Burma and Southeast Asia. Objective: The study was designed to find out the incidence of HbE/beta thalassaemia in BSMMU. Method: A total of 700 patients suspected to have been suffering from haemolytic anaemia were included in the study. Patients having evidence of haemolysis in peripheral blood film were selected for reticulocyte count and haemoglobin electrophoresis in cellulose acetate membrane at pH 8.6. Result: The study group of 700 patients underwent Hb-electrophoresis of which only 52 (7.4%) cases were diagnosed as HbE/beta thalassaemia. Out of 52 cases, 34 (65.4%) patients were found symptomatic and the remaining 18 (34.6%) patients were asymptomatic. Out of 34 symptomatic cases of HbE/beta thalassaemia, only 14 cases needed blood transfusion. Among the 14 patients, only 8 patients needed more than 10 units of transfusion and 6 patients needed frequent transfusion that is two units of blood in every month. Conclusion: It is clearly evident from the present and other studied so far carried out in this Indian subcontinent and South-East Asia that hereditary haemolytic anaemia due to globin chain defects are quite common in this region, especially in Bangladesh and are responsible for considerable morbidity and mortality. Key words: Thalassaemia; Haemoglobinopathies; HbE/beta thalassemia. DOI: 10.3329/bsmmuj.v2i2.4762 BSMMU J 2009; 2(2): 78-80